Prevalence of atrial fibrillation – a comprehensive nationwide analysis in Finland. (3rd October 2022) - Lehto, M; Haukka, J; Halminen, O; Mustonen, P; Putaala, J; Linna, M; Aro, A; Hartikainen, J; Airaksinen, K E J
Abstract: Introduction: Prevalence of atrial fibrillation (AF) is strongly associated with age, and with longer life-time expectancy number of AF patients is worldwide strongly increasing. However, nationwide prevalence of AF is not known when primary care data as well is accessible. Purpose: The FinACAF-study is a nationwide registry study including of all AF patients searched from all available national health care registers. To our knowledge, this is the first nationwide AF study including both primary, secondary, and tertiary health care register data. The aim of this study was to assess the prevalence of AF in unselected nationwide population in Finland. Methods: In the FinACAF study we gathered data of all AF patients (hospitalizations and outpatient specialist visits and primary health care, and National Reimbursement Register) from all national health care registers from 01st January 2004 to 31st December 2018. The annual prevalence on December 31st of each year 2007–2018 was calculated as the cumulative number of patients alive with AF divided by the number of Finnish population on the last day of that year. The prevalence is presented for population ≥20 years, and with the entire population as the background population, as well as for populations ≥65 years, and ≥75 years. Results: In total, 411, 387 patients with the diagnosis of AF were documented during 2004–2018 in Finland. The number of adult patients with AF at the end of the study period in 2018 was 226, 847, corresponding to an AF prevalence of 5.2% in the age group ≥20 years. The prevalence in the total Finnish population was 4.1%. The prevalence rates increased remarkably with increasing age and were higher in men compared to women (5.9% vs. 4.6%, p<0.001) in all age groups (Figure 1). The prevalence of AF in the adult population increased remarkably from 2.5% in 2007 to 5.2% in 2018 (p<0.001) (Figure 2). Among the population ≥65 years the prevalence in 2018 was 15.3%, and in the elderly, ≥75 years the prevalence of AF was 23.4%. Conclusions: Based on comprehensive, nationwide data – also including the primary care – we observed extremely increasing prevalence of AF in the older population, as well as remarkably increasing prevalence of AF over time. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Helsinki and Uusimaa Hospital District